Prevalence and determinants of depression, anxiety, and stress among secondary school students - Tingting Dong; Yumei Wang; Yuanjie Lin (PLoS ONE, 2025)
Background By investigating the depression, anxiety and stress status of secondary school students, we further analysed the influencing factors of the changes in depression, anxiety and stress among secondary school students, so as to provide references for subsequent studies and interventions on adolescent mental health. Methods This study was a cross-sectional research study conducted in a city in Southwest China. A questionnaire survey was conducted during March-June 2022 among students attending secondary schools within a city. The surveyed secondary schools were not categorized as public or private. It mainly investigated the general information of middle school students, Depression-Anxiety-Stress Scale (DASS-21), and assessed the mental health status of middle school students. Results A total of 2,716 secondary school students were surveyed, 1,230 males (45.29%) and 1,486 females (54.71%). Among them, 24.4% of the secondary school students had depressive symptoms, 41.4% had anxiety symptoms, and 15.6% had stress; Through logistic regression analysis, attending high school, ranking <60% in academic performance, little or no family psychological support and peer psychological support were the main influencing factors. Conclusion The present study demonstrated that the high school student population, students with an academic ranking of <60%, and students who lacked family/peer psychological support were at higher risk for mental health. These findings provide an empirical basis for developing graded intervention strategies for specific risk factors..